THE INFLUENCE OF COMPETENCE ON TEACHER PERFORMANCE MODERATED BY SCHOOL PRINCIPAL'S LEADERSHIP AT MADRASAH TSANAWIYAH AND ALIYAH ALWASLIYAH BINJAI CITY - Supriadi Supriadi; Mesra B (Berajah Journal, 2023)
The aim of this research was to analyze and investigate the role of school principals' leadership in moderating the relationship between competence and teacher performance at Madrasah Tsanawiyah and Aliyah Alwasliyah Binjai City. Good teacher performance is a key factor in achieving the school's goals. The research design employed in this study is quantitative associative. The location of the research was conducted in Binjai. The population in this study consists of 84 teachers. The sampling technique used was saturated sampling, where the entire population was taken as the sample. Data collection was carried out using a questionnaire. The data analysis in this study was performed using Smart PLS 3.0 with the Moderated Regression Analysis (MRA) model. The results of this study indicated that: 1) Competence significantly influences the teacher performance of Madrasah Tsanawiyah and Aliyah Alwasliyah Binjai City with a P-Value of 0.000 < 0.05, which means that if teacher competence increases, teacher performance also increases. 2) The moderating variable, which is school principals' leadership, was unable to strengthen significantly the influence of competence on teacher performance at Madrasah Tsanawiyah and Aliyah Alwasliyah Binjai City with a P-Value of 0.895 < 0.05. In other words, it can be stated that the hypothesis was rejected. was unable to significantly strengthen the influence of competence on teacher performance at Madrasah Tsanawiyah and Aliyah Alwasliyah Binjai City with a P-Value of 0.895 < 0.05. In other words, it can be stated that the hypothesis was rejected. was unable to significantly strengthen the influence of competence on teacher performance at Madrasah Tsanawiyah and Aliyah Alwasliyah Binjai City with a P-Value of 0.895 < 0.05. In other words, it can be stated that the hypothesis was rejected.